Intraductal Pneumatic Lithotripsy after Extended Transoral Duct Surgery in Submandibular Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2018)
Objective Persistent, residual, or recurrent stones after transoral duct surgery are always associated with hilar to intraparenchymal and/or multiple sialolithiasis, causing difficulties in the treatment. This study was performed to assess the value of intraductal lithotripsy in the treatment of persistent, residual, or recurrent sialolithiasis after extended duct surgery in the submandibular gland. Study Design Retrospective study covering February 2015 to June 2018. Study Setting Tertiary referral center for salivary gland diseases. Subjects and Methods After extended ductal surgery, 39 patients presenting with persistent, residual, or recurrent stones were treated. Four patients had persistent stones; 16 had residual stones; and 19 presented with recurrent stones. Among these patients, 50 stones were treated with intraductal pneumatic lithotripsy. Fragmentation rate, stone-free rate, and symptom-free rate after treatment with intraductal lithotripsy were outcome measures. Results Of the 39 patients, 97.4% became stone-free, and all were symptom-free. Ninety-eight percent of the stones were completely fragmented. For 23.1% of the patients, >1 stone was treated with intraductal lithotripsy. All patients with persistent stones, 93.7% of those with residual stones, and all with recurrent stones became stone-free and symptom-free. No severe complications developed. Conclusions This study shows that patients presenting with difficult and/or multiple sialolithiasis after extended transoral submandibular duct surgery can be treated with success rates >97%. For multiple sialolithiasis in particular, a multimodal treatment approach with interventional sialendoscopy and intraductal lithotripsy as a central element is a prerequisite for success, as this enables the most difficult part to be performed with high success rates.
EVALuna2:35383